Изучение микробиологических параметров полости рта у ортопедических больных с синдромом непереносимости - Придатко, И.С. (Таврический медико-биологический вестник, 2014)
Знімні пластинкові протези, адсорбуючи на своїй поверхні мікроби, ускладнюють теплообмін в
порожнині рота, сприяючи розмноженню мікроорганізмів і проникненню продуктів їх життєдіяльності в
підлеглі тканини, є причиною розвитку синдрому непереносимості до акриловим пластмасам, що
супроводжується запальними процесами в тканинах протезного ложа. Removable plate dentures are the cause of the syndrome of intolerance to acrylic plastics, accompanied
by inflammatory processes in the tissues of prosthetic bed, and have the ability to adsorb on its surface microbes,
inhibiting heat transfer in the cavity and contributing to the growth of microorganisms and penetration of products
of their activity into the tissues.